Efek Pemberian Nanoemulgel Ekstrak Moringa oleifera terhadap Jumlah Sel Makrofag Rattus norvegicus - Pratiwi, Ariyati Retno; Risnauli, Yanice Natalia Regar (Fakultas Kedokteran Gigi UB, 2026)
Introduction: Inflammation is a complex response of the body's immune system that refers to pathological conditions against various harmful stimuli. One of the factors causing inflammation is the presence of ulcers. At the beginning of the inflammatory response, macrophages tend to be polarized into the M1 phenotype (pro-inflammatory) then switch to the M2 phenotype (anti-inflammatory). The balance between M1 and M2 macrophage activity is essential for proper inflammation and optimal tissue repair. In the context of macrophage modulation, nanoemulgel formulation has the potential to increase the delivery of bioactive compounds from Moringa oleifera extract to target tissues, facilitate interactions with tissue macrophages, and enhance anti-inflammatory and immunomodulatory effects. Objective: This study aims to determine the effect of administering Moringa oleifera extract nanoemulgel on the number of Rattus norvegicus macrophage cells. Method: This study used a true experimental in vivo with a Randomized Post Test Only Control Group design using 24 male Wistar rats divided into 4 groups, 2 control groups and 2 treatment groups. The variables studied were the number of macrophage cells observed on the 5th day. Results: The results showed that Moringa oleifera extract nanoemulgel had an effect on the number of M1 Rattus norvegicus macrophage cells. This was evidenced by a significant increase in the number of M1 macrophage cells in the 30% Moringa oleifera extract nanoemulgel treatment group on the 5th day. Conclusion: After administering Moringa oleifera extract nanoemulgel, there was a difference in the number of macrophage cells in the inflammatory process observed on the 5th day.